Cell line-based in vitro models of normal and chronic bronchitis-like airway mucosa to study the toxic potential of aerosolized palladium nanoparticles - Ji, Jie; Jansen, Katja; Kessler, Vadim; Seisenbaeva, Gulaim; Gerde, Per; Malmlöf, Maria; Palmberg, Lena; Upadhyay, Swapna (Frontiers in Medicine, 2024)
Background Physiologically relevant cell line-based models of human airway mucosa are needed to assess nanoparticle-mediated pulmonary toxicity for any xenbiotics expsoure study. Palladium nanoparticles (Pd-NP) originating from catalytic converters in vehicles pose health risks. We aimed to develop in vitro airway models to assess the toxic potential of Pd-NP in normal (Non-CB) and chronic bronchitis-like (CB-like) mucosa models. Methods Bronchial mucosa models were developed using Epithelial cells (16HBE: apical side) co-cultured with fibroblast (basal side) at an air-liquid interface. Furthermore, both Non-CB and CB-like (IL-13 treatment) models with increased numbers of goblet cells were used. The models were exposed to 3 different doses of aerosolized Pd-NP (0.2, 0.3, and 6 μg/cm2) using XposeALI® and clean air as a control. After 24 h of incubation, the expression of inflammatory (IL6, CXCL8, TNFα, and NFKB), oxidative stress (HMOX1, SOD3, GPx, and GSTA1), and tissue injury/repair (MMP9/TIMP1) markers was assessed using qRT–PCR. The secretion of CXCL-8 and the expression of a tissue injury/repair marker (MMP-9) were measured via ELISA. Results Significantly (p < 0.05) increased expressions of CXCL8, IL6, and NFKB were observed at the highest dose of Pd-NP in CB-like models. However, in Non-CB mucosa models, a maximum effect on TNFα and NFKB expression was observed at a medium Pd-NP dose. In Non-CB mucosa models, SOD3 showed a clear dose-dependent response to Pd-NP exposure, while GSTA1 expression was significantly increased (p < 0.05) only at the lowest dose of Pd-NP. The secretion of CXCL-8 increased in a dose-dependent manner in the Non-CB mucosa models following exposure to Pd-NP. In CB-like models, exposure to high concentrations of Pd-NP significantly increased the release of MMP-9 compared to that in other exposure groups. Conclusion The combination of our Non-CB and CB-like mucosa models with the XposeALI® system for aerosolized nanoparticle exposure closely mimics in vivo lung environments and cell-particle interactions. Results from these models, utilizing accessible cell lines, will maximize the reliability of in vitro findings in human health risk assessment.